Binuclear Rhenium and Manganese Carbonyl Compounds Containing Hetero-Mercaptanes - Hoque, Md Anwarul; Miah, Md Arzu; Abser, md Nurul; Azad, Abul K; Khan, Kamrun N; Karim, Md Manzurul (Journal of the Bangladesh Chemical Society, 2012)
Treatment of 2-Mercaptothiazoline, 2-Mercaptobenzimidazole, 2-Mercapto-1- methylimidazole with [M2(CO)10] (M = Re and Mn) at ambient temperature in presence of decarbonylating reagent Me3NO give the complexes [Mn2(?-?2-C3H4NS2)2(CO)6] (1), [Re2(?-?2-C3H4NS2)2(CO)6] (2), [Mn2(?-?2-C7H5SN2)2(CO)6] (3), [Re2(?-?2- C7H5SN2)2(CO)6] (4), [Re2(?-?2-C4H5N2S)2(CO)6] (5) and [Re2(?1-C4H5N2SH)(CO)9] (6) respectively. All the compounds have been characterized by IR, 1H NMR and mass spectral data. The heterocyclic ligands are expected to be coordinated to two or single metal atom through the nitrogen and sulfur atoms or via only sulfur atom. DOI: http://dx.doi.org/10.3329/jbcs.v25i1.11775 Journal of Bangladesh Chemical Society, Vol. 25(1), 62-70, 2012>